2004
DOI: 10.1021/jm049932u
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 4-(1H-Imidazol-4(5)-ylmethyl)pyridine (Immethridine) as a Novel, Potent, and Highly Selective Histamine H3Receptor Agonist

Abstract: In this study, the piperidine ring of immepip and its analogues was replaced by a rigid heterocyclic pyridine ring. Many compounds in the series exhibit high affinity and agonist activity at the human histamine H(3) receptor. Particularly, the 4-pyridinyl analogue of immepip (1c, immethridine) is identified as a novel potent and highly selective histamine H(3) receptor agonist (pK(i) = 9.07, pEC(50) = 9.74) with a 300-fold selectivity over the closely related H(4) receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…At the hH 4 R these ligands also act as agonists, but exert somewhat lower intrinsic activity (␣ values of 0.9, 0.9, and 0.6, respectively) ( Table 3). As reported previously (Kitbunnadaj et al, 2004), the recently identified H 3 R agonist immethridine (pK i ϭ 9.1 Ϯ 0.1) binds much less potently to the hH 4 R (pK i ϭ 6.6 Ϯ 0.1) and is also not able to fully activate the H 4 R (Table 3). In agreement with our findings with N ␣ -methylhistamine, the methylated immepip analog methimepip shows a large selectivity for the hH 3 R (pK i ϭ 9.0 Ϯ 0.1) over the hH 4 R (pK i ϭ 5.7 Ϯ 0.1), as reported previously (Kitbunnadaj et al, 2005).…”
Section: Downloaded Fromsupporting
confidence: 71%
See 1 more Smart Citation
“…At the hH 4 R these ligands also act as agonists, but exert somewhat lower intrinsic activity (␣ values of 0.9, 0.9, and 0.6, respectively) ( Table 3). As reported previously (Kitbunnadaj et al, 2004), the recently identified H 3 R agonist immethridine (pK i ϭ 9.1 Ϯ 0.1) binds much less potently to the hH 4 R (pK i ϭ 6.6 Ϯ 0.1) and is also not able to fully activate the H 4 R (Table 3). In agreement with our findings with N ␣ -methylhistamine, the methylated immepip analog methimepip shows a large selectivity for the hH 3 R (pK i ϭ 9.0 Ϯ 0.1) over the hH 4 R (pK i ϭ 5.7 Ϯ 0.1), as reported previously (Kitbunnadaj et al, 2005).…”
Section: Downloaded Fromsupporting
confidence: 71%
“…Based upon our data, many imidazol-containing H 3 R ligands, including various H 3 R reference compounds, show potent H 4 R activities and should be treated with caution. More recently developed H 3 R agonists, such as immethridine (Kitbunnadaj et al, 2004) or methimmepip (Kitbunnadaj et al, 2005), or nonimidazole H 3 R antagonists, such as JNJ 6379490 (Ling et al, 2004) or A-349821 (Esbenshade et al, 2004), hardly act at the H 4 R and will therefore provide good tools to selectively target the H 3 R. In the series of tested H 3 R ligands, we have identified iodophenpropit as potent neutral H 4 R antagonist and the burimamide analog VUF 4742 as the second identified H 4 R inverse agonist. From the screening of H 2 R ligands, we have identified 4-methylhistamine as the first high-affinity H 4 R agonist (K i ϭ 50 nM) that has a Ͼ100-fold selectivity for the hH 4 R over the other histamine receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Other lipophilic agonists have also been described in an extensive SAR study (Govoni et al, 2006), and an agonist (37) (human H 3 receptor K i = 0.17 nM, 77% efficacy) was active in vivo in mice in blocking aggression and stress (Ishikawa et al, 2010). Other H 3 receptor agonists have been described with novel structural variations, including immethridine (human H 3 receptor K i = 0.9 nM, 90% agonist efficacy), an analog of immepip wherein the highly basic piperidine moiety is replaced by a less basic pyridinyl moiety (Kitbunnadaj et al, 2004). A particularly interesting ligand is the "protean" (Kenakin, 2002) agonist proxyfan (38) (Gbahou et al, 2003), a compound that does not fit neatly into a rigid categorization of agonist or antagonist, because its properties have been found to depend on the system assessing efficacy, with full agonism, neutral antagonism, and inverse agonism seen.…”
Section: E H 3 -Selective Ligandsmentioning
confidence: 99%
“…Since it is well documented that H 3 Rs are involved in histamine-mediated gastric protection in rats [for review, see [38]], it is conceivable to hypothesize that putative damaging effects of H 4 R agonists could be masked by H 3 R-mediated gastroprotective activity. However, unpublished data from our group showed that the highly selective H 3 R agonist immethridine [39] was not protective against the IND+BET-induced gastric damage in mice. Previous data in rats showed that both VUF8430 and VUF10460 significantly aggravated the ulcerogenic effect of 0.6 N HCl [32], thus suggesting that species (mouse vs. rat) and/or the type of ulcerogenic stimulus (IND vs. 0.6 N HCl) may be the key factor responsible for the lack of effects of H 4 R agonists observed in the present experiments.…”
Section: Discussionmentioning
confidence: 99%